First tests of the biased movable B4C-limiter in the Uragan-2M torsatron under RF and UHF wall conditioning - Glazunov, G.P.; Baron, D.I.; Bondarenko, M.N.; Burchenko, P.Ya.; Chechkin, V.V.; Chernyshenko, V.Ya.; Grigor’eva, L.I.; Konovalov, V.G.; Konotopskiy, A.L.; Kotenko, V.G.; Lozin, A.V.; Maznichenko, S.M.; et al. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The work describes the design of a multifunctional B4C-limiter, and reports preliminary results from experimental study of the limiter operated at steady-state and pulsed RF discharge cleaning regimes in the Uragan-2M torsatron.